Interdepartmental cooperation in the supply of public services for the development of sports in Moscow - D. A. Krasnyukov (Путеводитель предпринимателя)
A special role in the development of the sports sector is played by the organization of interaction of various structures that allow more efficiently provide services to the population. The author on the example of analysis of the activities of the sport Department is considering the principles of the organization of interdepartmental interaction.